A study of Concept of e vehicles in India - Mr Jai Prakash; Dr. S. S. Jadhav (Innovative Research Thoughts, 2022)
As the world's oil reserves deplete, several researchers are looking at alternative energy sources for hybrid cars. There is growing worry about the negative impacts of driving with fossil fuel. Battery, fuel cell (FC), super capacitor (SC), and photovoltaic cell (solar) are only some of the alternative energy sources being researched for use in automobiles. The future generation of transportation may use hybrid electric vehicles (HEVs) that draw power from a combination of various renewable energy sources. This paper delves into the many facets of HEVs, including their EMS, power conditioning, and propulsion systems. HEV also encompasses disciplines such as DC machine and vehicle system. The simulation and experimentation-based type models and techniques are described in depth. This table, along with the cited sources, summarizes the performance of different HEV system combinations. Diverse hybrid electric vehicle sources, models, energy management systems (EMS), etc., from various researchers are surveyed in this work. Based on this comprehensive analysis, it is clear that current technologies have the potential to provide satisfactory HEV performance; nevertheless, improvements are needed in areas such as dependability and intelligent systems. Consequently, many factors, challenges, and problems related to creating a sustainable next-generation hybrid vehicle have been brought to light in this review.